The Role of Using Social Media as a Mediator in the Influence of Competitive Advantage, Support from Superiors, and Competitive Pressure on SME Performance - Anastasia Riani Suprapti; Hunik Sri Runing Sawitri; Asri Laksmi Riani; Mugi Harsono; Intan Novela Quratul Aini; Suryandari Istiqomah (Journal of Current Studies in SDGs, 2027)
Abstract. This research aims to examine and analyze the influence of competitive advantage, superior support and competitive pressure on the performance of SMEs. Apart from that, it also tests the variableof social media use which is conceptualized as a mediator. The research population is SMEs in Solo Raya. Respondents were 91 SMEs, determined by convenience and data collected through an online survey. The analysis technique used is PLS-SEM. The things that underlie this research are phenomena that occur in the business world as well as the results of previous research which shows that the use of social media in business in developing countries continues to develop. In the face of increasingly sharp competition, currently the use of social media is considered a key strategy in SMEs. The results of this research prove that competitive advantage, superior support, and competitivepressure have a significant effect on SME performance, as in the model conceptualized at the beginning.By including the social media adoption variable as a mediator, it can be shown that the influence of superior support on SME performance is mediated by social media adoption. Social media adoption isnot proven to mediate the effect of competitive advantage on SME performance, nor the effect of competitive pressure on SME performance.